Upwelling Amplifies Ocean Acidification on the East Australian Shelf: Implications for Marine Ecosystems - Schulz, Kai G.; Hartley, Simon; Eyre, Bradley (Frontiers in Marine Science, 2019)
Frequent upwelling of deep, cold water, rich in dissolved inorganic nutrients and carbon dioxide but low in oxygen concentrations and pH, is well documented in eastern boundary systems. As a consequence, waters in vast areas of the continental shelf can turn corrosive to the mineral aragonite, vital to a number of marine organisms. This phenomenon is projected to become more severe with ongoing ocean acidification. Although upwelling is also known to occur in western boundary systems, the impact on present day aragonite saturation state (Ωarag) is virtually unknown, let alone for the decades to come. Here we identified 32 events during 18 weeks of continuous measurements in Cape Byron Marine Park, Australia, with prolonged drops in ocean temperature of up to 5°C, oxygen concentrations by 34%, pH by 0.12 and Ωarag by 0.9 in a matter of hours. Temperature, salinity and oxygen saturation during these events hint at a water mass from 200 to 250 m depth off the Central East Australian shelf. Extrapolating present day upwelling to a preindustrial setting shows that ongoing ocean acidification has already lead to the crossing of a number of biological and geochemical Ωarag thresholds. The future intensity of these events critically depends on carbon dioxide emission scenario, and might be even more pronounced in the Great Barrier Reef where current day shelf associated waters carry a stronger deep water signal (based on oxygen levels) than at the study location. Finally, the proposed use of artificially upwelled water to cool increasingly temperature-stressed coral reef communities will need to take its unique carbonate chemistry properties into account.